Impact of pharmacist counseling on the clinical outcomes in the management of type 2 diabetes mellitus outpatients admitted to a hospital - Rina, Habsyah; Nasution, Azizah; Khairunisa (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Type 2 Diabetes mellitus remains a global health problem due to its poor clinical outcomes, high morbidity, and mortality caused by many complicated problems, one of which is the ineffective role of pharmacists in providing counselling to DM patients Methods: This pre and post cohort study analyzed the impact of pharmacist counselling on the blood glucose level and glycosylated hemoglobin (HbA1C) of T2DM outpatients (n=88) admitted to Asahan General Hospital period June to December 2022. Counselling provided comprised the importance of medication adherence and non-pharmacological approaches. Characteristics, BGLs and HbA1C of the patients were extracted from their medical records before and after counselling using a predetermined questionnaire. Characteristics of the patients were descriptively analyzed. Results: The significance of the counselling on these outcomes was analyzed by applying Wilcoxon test (p <0.05 was considered significant). The mean age of the patients was 57.89±9.75 (years). Most (57.95%) of them were female. Proportion of the patients with controlled BGLs (%): before counselling, 27.7; after counselling, 89.8. Proportion of the patients with controlled HbA1C (%): before counselling, 27.3; after counselling, 89.8. Pharmacist counselling significantly improved the clinical outcomes of T2DM patients, p=0.000. Conclusions: Pharmacist counselling plays an important role to improve BGLs and HbA1C in T2DM patients which can finally improve their quality of life.